GPU Parallel Computing Algorithm in Target Tracking of Space - Ding, Tuo (Applied Mechanics and Materials, 2014)
Article careful analysis of existing processes and target tracking algorithm and part of the video image processing algorithm that consume large amount of data based CPU. Each algorithm for image pre-processing module and tracking module algorithm designed operational processes. Several studies algorithm for image pre-processing module, and each was carried out in parallel GPU accelerated processing, and were tested in a unified CUDA computing device. Experimental data show that some parts of the algorithm can be improved after the adoption of CUDA target tracking algorithm optimized overall efficiency, has some practical significance.